Zinc–Air Batteries: Cobalt‐Encapsulated Nitrogen‐Doped Carbon Nanotube Arrays for Flexible Zinc–Air Batteries (Small Methods 1/2020). Issue 1 (9th January 2020) - Liu, Lina; Wang, Yue; Yan, Feng; Zhu, Chunling; Geng, Bo; Chen, Yujin; Chou, Shu‐lei
Abstract : In article number 1900571 by Chunling Zhu, Yujin Chen, Shu‐lei Chou, and co‐workers, flexible zinc–air batteries assembled with cobalt nanoparticles encapsulated in nitrogen‐doped carbon nanotube arrays show excellent electrochemical performance, which can power portable devices under extreme bending conditions.